Adult Cardiac Surgery During Covid-19 Pandemic - Laksono, Gerardo AK; Hutama, Andreas MS; Tahalele, Paul L (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2020)
Coronavirus Disease 2019 (COVID-19), which is caused by the SARS Coronavirus 2 (SARS-CoV-2), has affected over 200 countries worldwide. First case of COVID-19 wasfound in Wuhan, China, precisely around December 2019. COVID-19, especially in thosewith underlying health conditions or comorbidities, has an increasingly rapid and severeprogression, often leading to death. This virus is a single-strand RNA coronavirus, binding the angiotensin-converting enzyme 2 (ACE2) receptor which enters human cells. Coronavirusdisease has been reported to affect cardiac and vascular organs. cardiomyocyte death andinflammation are results of a direct mechanism that involves viral infiltration into myocardialtissue. Some cardiovascular manifestations of myocardial injuries associated with COVID-19are arrhythmias, myocardial infarction, heart failure, and elevated biomarkers (cardiactroponin I and brain-type natriuretic peptide). Some of this manifestation requires immediate intervention or surgery. Criteria are needed for hospitals or institutions that mostly maintain cardiac surgery services and surgery-urgent patients depending on severity of the disease and hospital resources. These criteria also limit the risk of exposure to patients and healthcare workers and allocate resources appropriately to those in greatest need. This paper aims to share our discussion and give an overview of patients undergoing cardiac surgery, providing clinicians with recommendations to triage and plan these procedures during the COVID-19 outbreak effectively.